A Study of the Contribution of Nearest-Neighbour Thermodynamic Parameters to the DNA Sequences Generated by Ant Colony Optimisation - Mohd Zaidi, Mohd Tumari; Zuwairie, Ibrahim; Kamarul Hawari, Ghazali; Faradila, Naim; Mohd Falfazli, Mat Jusof; Ismail, Ibrahim; Zulkifli, Md. Yusof; Kamal, Khalil; Muhammad Arif, Abdul Rahim; Sophan Wahyudi, Nawawi (2013)
The process of designing a set of good DNA sequences is an essential problem and one of the most practical and important research topics in DNA-based computing and the DNA nanotechnology area. In this field of research, a DNA sequence design problem is defined as a multi-objective problem, and it is evaluated using four objective functions, h-measure, similarity, continuity and hairpin. In addition, two constraints, GC content and melting temperature (Tm), are used to maintain uniform chemical characteristics of the sequences. In the authors’ previous research, an ant colony system (ACS) was proposed to solve the DNA sequence design problem based on nearest neighbour. The Watson-Crick base pair ∆Go37 was used as the distance between nodes for the thermodynamic parameters in the problem models for the heuristic approach in the ACS algorithms. In the current study, a non-heuristic approach and four new models using the heuristic approach are proposed, and results from the models are compared.